The Relationship between Neighborhood Disorder, Social Networks, and Indoor Cigarette Smoking among Impoverished Inner-City Residents - Latkin, Carl A. (J Urban Health, 2017)
Impoverished urban neighborhoods tend to have higher rates of smoking and higher rates of exposure to secondhand smoke as compared to more affluent neighborhoods. Contextual factors of neighborhood disorder and social network and household composition may have an impact on indoor smoking behaviors. The TIDE study examined psychosocial factors associated with smoking behaviors among impoverished inner-city smokers in Baltimore, Maryland. Among a community-recruited sample of 413 smokers who lived with others, most (73%) reported that they or others smoked in their residence. Cohabitation with children, elderly, and those with asthma and other respiratory condition was not associated with indoor smoking. Neighborhood disorder, the proportion of social network members who smoked with the study participant, and the proportion of household members who smoked were all independently associated with smoking indoors. The study findings suggest the importance of addressing neighborhood and social network factors when developing programs for promoting indoor smoking bans as well as cessation and prevention programs.